2017
DOI: 10.1152/ajplung.00050.2017
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic blockade of CD54 attenuates pulmonary barrier damage in T cell-induced acute lung injury

Abstract: Acute respiratory distress syndrome (ARDS) is a serious, often fatal condition without available pharmacotherapy. Although the role of innate cells in ARDS has been studied extensively, emerging evidence suggests that T cells may be involved in disease etiology. enterotoxins are potent T-cell mitogens capable of triggering life-threatening shock. We demonstrate that 2 days after inhalation of enterotoxin A, mice developed T cell-mediated increases in vascular permeability, as well as expression of injury marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 87 publications
1
12
0
Order By: Relevance
“…Similar upregulation is observed in Ang II-induced macrophage infiltration and cardiovascular pathology, which is ameliorated by ICAM-1 blockade (Lin Q. Y. et al, 2019). Blockade of ICAM-1 is also reported to markedly reduce pulmonary barrier damage in ARDS (Svedova et al, 2017).…”
Section: Adhesion and Tissue Retention Of Inflammatory Leukocytesmentioning
confidence: 56%
“…Similar upregulation is observed in Ang II-induced macrophage infiltration and cardiovascular pathology, which is ameliorated by ICAM-1 blockade (Lin Q. Y. et al, 2019). Blockade of ICAM-1 is also reported to markedly reduce pulmonary barrier damage in ARDS (Svedova et al, 2017).…”
Section: Adhesion and Tissue Retention Of Inflammatory Leukocytesmentioning
confidence: 56%
“…Both systemic and intranasal exposure to SEB cause acute lung injury, characterized by increased expression of adhesion molecule ICAM-1 and vascular cell adhesion molecule (VCAM), increased neutrophils and mononuclear cell infiltrates, endothelial cell injury, and increased vascular permeability [28,33,115]. A blockade of ICAM-1 by anti-ICAM-1 antibodies attenuated pulmonary barrier damage in a murine model of SEA-mediated acute lung injury [121].…”
Section: Contributions By Other Cytokines and Chemokinesmentioning
confidence: 99%
“…Cell activation induces ER stress, oxidative stress, mitochondrial ROS, and damage, which also promotes cell death. An upregulation of damage response genes contributes to the irreversible multiorgan damage seen in animal models of superantigen-induced toxic shock and human toxic shock syndrome [33,98,115,121,143,144,145]. In this regard, superantigen-induced mTORC1 activation increases oxidative stress, contributing to inflammation, DAMPs, and cell death.…”
Section: Lessons Learned From Therapeutics That Prevent Seb-inducmentioning
confidence: 99%
“…Thus, it will be important to determine the identity of the binding site of enterotoxin A on AMs as well as the processing of the enterotoxin by these phagocytes. Previous studies showed that following intranasal S. aureus enterotoxin exposure, mice experience a systemic oligoclonal T cell activation and cytokine release to blood (26,33,51). To examine the role of AMs in the enterotoxin A-induced inflammatory response, WT and CD169-DTR mice were treated with DT and 2 d later, they were exposed to vehicle or enterotoxin A.…”
Section: Discussionmentioning
confidence: 99%
“…Harvest and processing of bronchoalveolar lavage (BAL) fluid, lung, and spleen, and staining for flow cytometry were performed as described previously (26,33). The single-cell suspensions were labeled with Live/Dead fixable blue dead cell stain (Thermo Fisher Scientific, Waltham, MA) and stained with the following Abs: CD45.2 clone 104 (shown as CD45), anti-Siglec F clone E50-2440, anti-CD11c clone N418, anti-CD169 clone SER-4, anti-CD3 clone 17A2, anti-Vb3 clone KJ25, anti-Vb14 clone 14-2, anti-CD25 clone PC61, and anti-CD69 clone H1.2F3 (purchased from BD Biosciences, San Jose, CA or eBioscience, San Diego, CA).…”
Section: Flow Cytometrymentioning
confidence: 99%